Respuesta :

Answer:

(x=4.0 Y=1.0)

Step-by-step explanation:

Here you go

Answer:

(- 4, 1 )

Step-by-step explanation:

Given the 2 equations

2.5x - 3y = - 13 → (1)

3.25x - y = - 14 → (2)

Multiplying (2) by - 3 and adding to (1) will eliminate the term in y

- 9.75 + 3y = 42 → (3)

Add (1) and (3) term by term

- 7.25x = 29 ( divide both sides by - 7.25 )

x = - 4

Substitute x = - 4 in either of the 2 equations and solve for y

Substituting in (1)

- 10 - 3y = - 13 ( add 10 to both sides )

- 3y = - 3 ( divide both sides by - 3 )

y = 1

Solution is (- 4, 1 )